2015
DOI: 10.1177/0310057x1504300408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-Guided Supraclavicular, Infraclavicular and Below-C6 Interscalene Brachial Plexus Block for Upper Limb Surgery: A Randomised, Observer-Blinded Study

Abstract: This prospective, randomised, observer-blinded study was conducted to compare the ease of performance and surgical effectiveness of interscalene block below the C6 nerve root with supraclavicular and infraclavicular techniques of brachial plexus block for upper arm and forearm surgery. Sixty adult patients of American Society of Anesthesiologists grade 1 to 3, undergoing upper limb surgery, were randomly allocated into three groups. Group SC received supraclavicular blockade, group IC received infraclavicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is the gold standard for describing the BP and its terminal branches (Boykin et al, ; Chalian et al, ; Ahlawat et al, ; Marquez Neto et al, ; Wang et al, ). During the last two decades, ultrasonography (US) of the suprascapular portion of the SSN has gained prominence for the dynamic exploration of neuropathies and for ultrasound‐guiding of anesthetic nerve blocks in cases of acute and chronic shoulder pain (Karataş et al, ; Boykin et al, ; Chan et al, ; Stein et al, ; Bharti et al, ; Lewis et al, ; Chang et al, ; Dhir et al, ). The trajectory of the SSN at the level of the suprascapular notch is deep, inconsistent and in the vicinity of the suprascapular artery; these factors make ultrasound‐guided procedures more challenging (Harmon and Hearty, ; Vorster et al, ; Siegenthaler et al, ; Battaglia et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) is the gold standard for describing the BP and its terminal branches (Boykin et al, ; Chalian et al, ; Ahlawat et al, ; Marquez Neto et al, ; Wang et al, ). During the last two decades, ultrasonography (US) of the suprascapular portion of the SSN has gained prominence for the dynamic exploration of neuropathies and for ultrasound‐guiding of anesthetic nerve blocks in cases of acute and chronic shoulder pain (Karataş et al, ; Boykin et al, ; Chan et al, ; Stein et al, ; Bharti et al, ; Lewis et al, ; Chang et al, ; Dhir et al, ). The trajectory of the SSN at the level of the suprascapular notch is deep, inconsistent and in the vicinity of the suprascapular artery; these factors make ultrasound‐guided procedures more challenging (Harmon and Hearty, ; Vorster et al, ; Siegenthaler et al, ; Battaglia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the gold standard for describing the BP and its terminal branches (Boykin et al, 2010;Chalian et al, 2011;Ahlawat et al, 2015;Marquez Neto et al, 2016;Wang et al, 2016). During the last two decades, ultrasonography (US) of the suprascapular portion of the SSN has gained prominence for the dynamic exploration of neuropathies and for ultrasound-guiding of anesthetic nerve blocks in cases of acute and chronic shoulder pain (Karataş et al, 2002;Boykin et al, 2010;Chan et al, 2011;Stein et al, 2012;Bharti et al, 2015; Additional Supporting Information may be found in the online version of this article. Lewis et al, 2015;Chang et al, 2016;Dhir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the onset time of the ISB was longer and it was associated with an unacceptable incidence of phrenic nerve palsy [17].…”
Section: Upper Limb Brachial Plexus Blocksmentioning
confidence: 99%
“…The supraclavicular approach to the brachial plexus block was first described in the early 20 th century and is arguably the most preferred brachial plexus (BP) approach with the highest success rate. 1 With this approach, the trunks/divisions of the BP are compact and superficial to the skin making it easy to visualise on ultrasound. 1 Due to the limited surface area, the entire BP is anaesthetised.…”
Section: Introductionmentioning
confidence: 99%
“…1 With this approach, the trunks/divisions of the BP are compact and superficial to the skin making it easy to visualise on ultrasound. 1 Due to the limited surface area, the entire BP is anaesthetised. The supraclavicular block also has the most widespread extent of sensory blockade among all the BP approaches and is ideal for providing dense, rapid onset, and efficient anaesthesia and analgesia for procedures from the shoulder joint and mid-humerus proximally, to the hand distally.…”
Section: Introductionmentioning
confidence: 99%